2021
DOI: 10.47253/jtrss.v4i1.581
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Caring Practices of Songbird, Red-Whiskered Bulbul (Pycnonotus jocosus)

Abstract: Pycnonotus jocosus is known as red-whiskered bulbul or known by local Malaysian as songbird or burung candik. Burung candik is one of the favourite pet birds’. Generally, it comes from Bangladesh, southern China, India, Nepal, north Peninsular Malaysia, Thailand and Vietnam (Animal Pest Alert: Red-whiskered Bulbul). Burung candik is favoured because of their ability in singing in east-coast region of Malaysia specifically. In this research, the caring practices are observed. All the result were recorded and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Point counts were conducted from September 2019 to February 2020, during the non‐breeding season in Spain, to determine the presence of the species in the squares (Figure 1). The species sings frequently during the day throughout the year, which is one of the reasons why it is captured and traded (To et al, 2021; Zulhisyam et al, 2016). Domínguez‐Pérez and Gil‐Delgado (2022), in a previous study, demonstrated that the species can be readily detected in the field under similar sampling conditions in just 5 min and it can be heard from nearly 100 m away.…”
Section: Methodsmentioning
confidence: 99%
“…Point counts were conducted from September 2019 to February 2020, during the non‐breeding season in Spain, to determine the presence of the species in the squares (Figure 1). The species sings frequently during the day throughout the year, which is one of the reasons why it is captured and traded (To et al, 2021; Zulhisyam et al, 2016). Domínguez‐Pérez and Gil‐Delgado (2022), in a previous study, demonstrated that the species can be readily detected in the field under similar sampling conditions in just 5 min and it can be heard from nearly 100 m away.…”
Section: Methodsmentioning
confidence: 99%